THE IMPLEMENTATION OF TASK-BASED INSTRUCTION IN TEACHING SPEAKING - Mutiara Stepani (Universitas Kuningan, 2016)
This study aims at investigating the benefits and challenges encountered by the teacher and the students in implementing task-based instruction. This study mainly utilizes a qualitative research design covering the trait of a case study. This study was carried out in one vocational high school in Bandung involving one class from the eleventh grade students. The data were collected through interview and questionnaires. The data from classroom interview and questionnaires were analyzed qualitatively. The result of interview and questionnaires revealed that task-based instruction resulted in some benefits and challenges. It was revealed that task-based instruction contributes to students speaking skill and enhances students participation. Apart from those benefits, some challenges were also found in terms of teachers competence, availability of time, and mixed ability students. Accordingly, it is recommended that this method is implemented in a long period of time.